The Intersection of Media Affordance and Religion: A Thematic Analysis of the Islamic Coverage of the Taliban’s Official Organ Shariat Newspaper - Pamirzad, Qurban Hussain; Susyal, Ghulam Ahmad; Joya, Mujiburrahman (Journal of Islamic Communication Studies, 2024)
The relationship between religion and media has been one of the topics of research interest. This study employed the media affordance concept and explored the religious coverage of the Shariat newspaper, which is the official organ of the Taliban government. The study examines how the official organ of the Taliban government covers and contributes to Islamic content dissemination and how it is used to distribute its ideology. Employing a mixed quantitative and qualitative analysis, this study found that the Taliban used the media's spatiotemporal, technological, and socio-lingual affordances to spread their narrative and Islamic issues through this publication. At the same time, through thematic analysis, this study noticed that Islamic topics susceptible to multi-interpretability were also covered in this newspaper. However, the quality of the content published might not be convincing and comprehensive enough for the reader who wants to satisfy their curiosity. In addition, it was noticed that a selective approach was employed in writing these issues to serve ideological justification.